PERENCANAAN JARINGAN AIR BERSIH DESA DIENG KEJAJAR WONOSOBO - Ashal Abdussalam; Akhmad Lutfatul Latif (Universitas Bandar Lampung, 2018)
Water is a basic need for human life, because water is a very important macro nutrient. Clean water is water that is used for daily needs whose quality meets health requirements and becomes drinking water after being cooked first. Dieng Village, Kejajar Subdistrict, Wonosobo Regency is a village that has a contour of hilly land and also has abundant springs. From the information of the local residents, the condition of the well water that they use everyday is possible to have contaminated sulfur based on the aroma felt by the community. So that clean water planning is needed for the community to replace unhealthy well water. The data used as a basis for making journals are grouped into two types, namely primary data and secondary data. From observations and observations it is known that the spring discharge is 1.5 l / second. This figure is enough to meet the water needs of the population for the next 15 years which is approximately 2.73 l / sec with a total user of 1,488 people. Supporting buildings are planned by calculation and pay attention to the situation in the actual location. From this, broncaptering buildings were obtained with dimensions of 2m x 2m x 1.5m and building buildings with dimensions of 4m x 4m x 3m. The total cost needed to implement this plan is Rp. 915,195,894.16.- at a price of Rp. 4,100.00.- per m3.